The Authority of Notaries in Executing Deeds Beyond Their Official Jurisdiction: A Study of the Principle of Territoriality and Legal Certainty - Abrori, Khayan; Adjie, Habib (Dinasti Research, 2026)
This study aims to analyze the authority of Notaries in executing deeds outside their official jurisdiction based on the principles of territoriality and legal certainty. The issue arises because, in practice, some Notaries draft deeds beyond their designated jurisdiction as determined in their appointment decree, which normatively contradicts Article 18 of Law No. 2 of 2014 concerning Notary Office. This situation raises legal concerns regarding the validity of the deed and the accountability of the Notary as a public official. This research employs a normative juridical method with statutory, conceptual, and case approaches. The statutory approach examines the relationship between the territorial principle and the implementation of notarial authority. The conceptual approach explores theories of competence and legal certainty, while the case approach reviews several Supreme Court decisions addressing the overreach of notarial jurisdiction. The findings indicate that executing a deed outside the official jurisdiction constitutes an ultra vires act, reducing the authenticity of the deed and potentially rendering it void. Therefore, strengthening regulations and supervisory mechanisms by consistently applying the territorial principle is essential to ensuring legal certainty and protecting good-faith parties.